2015
DOI: 10.13057/ijap.v5i01.260
|View full text |Cite
|
Sign up to set email alerts
|

Weber’s electrodynamics for the hydrogen atom

Abstract: <p>The original Weber action at a distance theory is valid for slowly varying effects, and it in addition to predicting all of the usual electrodynamical results, leads to crucial effects where the Maxwell theory fails. The Weber’s approach is an alternative to <a title="Maxwell's Equations" href="http://en.wikipedia.org/wiki/Maxwell%27s_Equations">Maxwell electrodynamics</a>, where the <a title="Coulomb's Law" href="http://en.wikipedia.org/wiki/Coulomb%27s_Law">Coulomb's law</a> … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…It has been demonstrated that it is consistent with Maxwell's equations [54][55][56][57][58]. Research into Weberian electrodynamics has received a significant contribution from Assis [38,55,[59][60][61] and has been applied to several pure and applied problems [43,52,57,[62][63][64][65][66][67][68][69][70][71].…”
Section: Resultsmentioning
confidence: 92%
“…It has been demonstrated that it is consistent with Maxwell's equations [54][55][56][57][58]. Research into Weberian electrodynamics has received a significant contribution from Assis [38,55,[59][60][61] and has been applied to several pure and applied problems [43,52,57,[62][63][64][65][66][67][68][69][70][71].…”
Section: Resultsmentioning
confidence: 92%
“…with the unknown parameters a 11 , a 12 , a 21 , and a 22 8 . Because the pilot tone of the FM signal is used, the s(t) signals are sinusoidal.…”
Section: Tests and Measurement Resultsmentioning
confidence: 99%
“…Recently, research interest in Weber electrodynamics has increased, where Weber's force has not only been applied to electron beam deflection [35][36][37], but also to other electromagnetic phenomena, such as induction [38][39][40], and superconductivity [41,42]. Moreover, the theory has further been connected to the fine structure of the hydrogen atom [43,44] and even Planck's constant [45,46]. We will thus show how our model can predict accurate beam trajectories.…”
Section: Mathematical Modellingmentioning
confidence: 92%